Dampak Pelaksanaan Programa Penyuluhan Pertanian terhadap Kapasitas dan Ketahanan Ekonomi Petani Padi Sawah di Lingkungan Amohalo Kelurahan Baruga Kecamatan Baruga Kota Kendari Provinsi Sulawesi Tenggara - Indah Paratu; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
Today's community-based development can be seen as one of the new paradigms in rural and agricultural development. Sustainable development, especially in rural areas, is pursued through increasing community empowerment and independence in realizing prosperity in all aspects of community life including the economic, socio-cultural, political and environmental fields. Community resilience is a process related to the capacity of the community after receiving a program or activity from a community empowerment program. In addition, community resilience is related to the adaptability of the community after receiving collective knowledge and skills and using the inherent capacity of individuals and communities in dealing with problems, so that community resilience is a concept that is currently used as an instrument of sustainable development. This study aims to determine the impact of implementing agricultural extension programs on the capacity and economic resilience of lowland rice farmers in the Amohalo neighborhood. This study uses a qualitative method. The process of collecting data was carried out by means of observation, interviews, literature studies and document studies. The results showed that the agricultural extension program implemented in the Amohalo Environment contributed to capacity building as seen by the increase in knowledge, attitudes and skills as well as institutional capabilities, especially cooperation and participation. Capacity building from the delivery of agricultural extension materials also builds community resilience in the Amohalo Environment, including the economic aspect consisting of a diverse & creative economy and income.